Managerial Accountability of Village-Owned Enterprise Wija Sari: A Case Study Research - Sari, Desak Made Mya Yudia; Sudana, I Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020)DO - 10.24843/JIAB.2020.v15.i02.p02, 2020)
This study aims to provide an in-depth understanding of a specific phenomenon and real situation regarding managerial accountability of Village-Owned Enterprise (BUMDesa) Wija Sari in Samsam Village. The methodology of this research is a descriptive interpretive employing Yin’s case study research approach. Qualitative data were collected through observations, interviews and documentation. The results of the study showed that the managerial accountability in BUMDesa Wija Sari in Samsam Village has been adopting practices with characteristics of transparency, honesty, integrity and consistency. Additionally, BUMDesa Wija Sari in Samsam Village also applies the characteristics of participation, sustainability, family and loyalty in the stage of planning, implementation and reporting. Keywords: Accountability, BUMDesa, planning, implementation, reporting.